Yield attributes, yields and nutrient uptake of Basmati rice (Oryza sativa) as influenced by in-situ and ex-situ green manuring crops and zinc fertilization - YADAV, DEVIDEEN; SHIVAY, Y S; SINGH, Y V; SHARMA, V K; BHATIA, ARTI (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted in a split plot design at the research farm of ICAR-Indian Agricultural Research Institute (IARI), New Delhi during summer and kharif seasons of 2015 and 2016 to study the influence of in-situ and ex-situ green manuring and zinc fertilization on nutrient uptake, yield attributes, correlation between yield and yield attributes, and yield of Basmati rice (Oryza sativa L.). Results of this study revealed that the incorporation of Sesbania aculeata green manure @ 33.8 and 35.6 t/ha prior to transplanting of Basmati rice during 2015 and 2016, respectively resulted in higher yield attributes and yield of Basmati rice compared with Vigna umbellata, Leucaena leucocephala and summer fallow during both the years. Foliar application of 0.5% solution of chelated Zn-EDTA at 20, 40, 60 and 80 days after transplanting (DAT) was better than soil application of Zn with regard to yield attributes and yield of Basmati rice and uptake of nutrients by the crop. In general, there was significant and positive correlation of grain yield with yield attributes. The uptake of nutrients by the crop was highest with incorporation of Sesbania aculeata and lowest in summer fallow.